Neighbourhood, crime and fear: Exploring subjective perception of security in Serbia - Marković Aleksandra; Filipović Božidar (NBP: Nauka, bezbednost, policija)
The perception of (in)security plays a crucial role in shaping individuals' interactions with their environment and can have significant implications for the prevalence and persistence of criminal activity within communities. Perceived insecurity can lead individuals to fear becoming victims of crime and can affect the willingness of individuals to report crimes to authorities. Furthermore , it can undermine social cohesion within communities by eroding trust and cooperation among residents. The subjective security experience in the neighbourhood is a multifaceted phenomenon influenced by various determinants. Using data from the European Social Survey Round 10, the paper aims to scrutinise the potential factors contributing to feelings of security among the respondents in Serbia. We focus on the respondents' perceptions of security in four regions (Bel-grade, Vojvodina, Šumadija and West Serbia, and South and East Serbia) operationalised through the question "How safe do you-or would you-feel walking alone in your neighbourhood after dark?". By examining determinants such as age, gender, daily activity, area (rural or urban), social capital, interpersonal trust and perceived quality of society, this paper aims to shed light on the complexities of security perception. The primary findings underscore the significance of individual vulnerability and social integration measures as critical indicators of security perceptions in the neighbourhoods. The study highlighted notable regional variations in predictors of security perceptions , emphasising the necessity of localised approaches to address security concerns. By comprehensively understanding the determinants of subjective security, policymakers and urban planners can develop targeted strategies to mitigate fear and enhance security perceptions.